Hong Kong SAR : Meeting the Challenges of Integration with the Mainland - Lee, William (Occasional Papers; Occasional Paper ;, 2004)
This Occasional Paper provides an overview of the main challenges facing Hong Kong SAR as it continues to become more closely integrated with the mainland of China. Section I provides an overview of recent macroeconomic developments and the main policy issues in Hong Kong SAR. Section II examines various aspects of the ongoing integration with the mainland, and the associated implications for the structure of the economy, and for macroeconomic and structural policies. Section III examines the medium-term fiscal outlook under different policy scenarios and discusses alternative policy options to restore fiscal balance. Section IV reviews recent developments in the real estate sector and their macroeconomic impacts. Section V presents an econome tric analysis of deflation and its determinants. Section VI examines the factors behind, and the implications of, rising wage inequality in Hong Kong SAR. Section VII presents an overview of recent developments in the financial sector and provides an assessment of Hong Kong SAR's prospects as an international financial center.